Attractiveness of Central and Eastern European Countries for Foreign Direct Investment in the Context of European Integration: The Case of Estonia - Kairi Andresson; Janno Reiljan; Ele Reiljan (European Regional Science Association (ERSA), 2001)
Foreign direct investment (FDI) flows in the world have increased rapidly during the last decade. Most of the FDI inflows are targeted to developed countries (78% in 1999, about fifth of the flows are going to developing countries and Central and Eastern European transition countries are the host countries for only 2% of the world FDI. The necessity of foreign investments in the transition countries is the result of industrial restructuring in post-socialist Eastern Europe and the Baltic countries. New markets, lower production costs and higher profit rates have been the main motivators in investing to the transition countries. Privatization programs of some of these countries have also facilitated foreign direct investments. Lankes and Venables (1996) and Lankes and Stern (1998) have noted that previous studies have shown predominance of market seeking investors in Central and Eastern European countries and factor cost considerations appeared to be of less importance for the majority of investments. A study by Meyer (1995) showed also that local market of Central and Eastern European countries is the primary motive in making foreign direct investments and factor costs played only a secondary role in investing to those markets at the beginning of the transition process. Several other studies (for example Barrell et al. 1999; Borsos-Torstila 1998; Éltetö 1999, Garibaldi et al. 1999; Guimaraes et al. 1997; Holland et al. 1998a, 1998b; Wang et al. 1995; Ziacik 2000 have also shown the significance of the determinants that are important for these types of investors in explaining the foreign investments' flows into the transition countries. Two other types of foreign investors are not so important due to the relative lack of natural resources and strategic assets in Central and Eastern European transition countries. However, it has to be considered that there are quite big differences in the shares of different types of foreign investors between countries and sectors. A number of Central and Eastern European transition countries are in the middle of process of integration to the European Union now. Economic integration has impact on the movement of the foreign direct investment. The main aim of this paper is to find out the possible changes in attractiveness of investment climate of the Central and Eastern European transition countries in the context of European integration. Taking into account this aim, paper is divided into four parts: * At first, theoretical foundations of foreign direct investments movements and results of the previous empirical research are presented. * Then, theoretical foundations of the impact of regional integration on foreign direct investment flows is discussed. * After this, determinants of FDI inflows in Central and Eastern European countries and in Estonia are analyzed by using generalized component, regression and multinominal logistic analysis, * Finally potential changes in attractiveness of the Central and Eastern European transition countries are discussed and some economic-political recommendations for the governments are presented. REFERENCES: 1. Barrell, R., Pain, N. Trade Restraints and Japanese Direct Investment Flows. - European Economic Review, 1999, Vol. 43, pp. 29-45. 2. Borsos-Torstila, J. Determinants of Foreign Direct Investment Operations of Finnish Multinational Companies in Transition Economies in 1990-1995. Helsinki, 1998, 180 p. 3. Ëltetö, A. The Impact of FDI on the Foreign Trade of Central European Countries. – Materials of the workshop "Impact of Foreign Direct Investment on the International Competitiveness of CEEC Manufacturing and EU Enlargement", Budapest, November 19-20, 1999, 23 p. 4. Garibaldi, P., Mora, N., Sahay, R., Zettelmeyer, J. What Moves Capital to Transition Economies? – Materials of the IMF Conference "A Decade of Transition: Achievements and Challenges", February, 1999, 49 p. 5. Guimaraes, P., Rolfe, R.J., Doupnik, T., Woodward, D.P. The Locational Determinants of Foreign Direct Investment in Central Europe. – SSRN Journal, 1997, July, 17 p. 6. Holland, D., Pain, N. The Determinants and Impact of Foreign Direct Investment in the Transition Economies: A Panel Data Analysis. – Materials of the conference “Convergence or Divergence: Aspirations and Reality in Central and Eastern Europe and Russia” Buckinghamshire, 1998a, pp. 300-325. 7. Holland D., Pain, N. The Diffusion of Innovations in Central and Eastern Europe: A Study of the Determinants and Impact of Foreign Direct Investment. – Materials of the conference “Convergence or Divergence: Aspirations and Reality in Central and Eastern Europe and Russia”, Buckinghamshire, 1998b, 49 p. 8. Lankes, H.-P., Stern, N. Capital Flows to Eastern Europe and the Former Soviet Union. – EBRD Working Paper, 1998, No. 27, 31 p. 9. Lankes, H.-P., Venables, A.J. Foreign Direct Investment in Economic Transition: The Changing Pattern of Investments. – Economies of Transition, 1996, Vol. 4, No. 2 pp. 331-347. 10. Meyer, K. Direct Foreign Investment in Eastern Europe: The Role of Labor Costs. - Comparative Economic Studies, 1995, Vol. 37, No. 4, pp. 69-88 (cited by http://www.ebscohost.com pp. 1-16). 11. Wang, Z.Q., Swain, N.J. The Determinants of Foreign Direct Investment in Transforming Economies: Empirical Evidence from Hungary and China. – Weltwirtschaftlisches Archiv, 1995, Band 131, pp. 359-382. 12. Ziacik, T. An Assessment of the Estonian Investment Climate: Results of a Survey of Foreign Investors and Policy Implications. – BOFIT Discussion Papers, 2000, No. 3, 52 p.
Keywords: 330